Aliens in the nursery : assessing the awareness and attitudes of Cape Town nursery managers in regard to invasive species regulations - Cronin, Kate (Department of Biological Sciences, 2015)
The horticultural industry is recognised as one of the major pathways for the introduction and spread of invasive alien plants (IAPs). In recognition of this, the South African government has recently enacted a new set of Alien and Invasive Species regulations, under the National Environmental Management Biodiversity Act (NEMBA), that are intended, in part, to improve controls on the horticultural industry's role in the spread of IAPs. In order to assess, and possibly enhance, the likely effectiveness of NEMBA, it is critical to build an understanding of stakeholders' awareness and attitudes towards the control of IAPs and associated regulatory policies. A two-pronged approach – involving nursery manager interviews (n=30) and plant stock audit assessments (n=41) - was used to gauge the awareness, compliance and attitudes of Cape Town nursery managers towards the NEMBA regulations. Results showed that less than ten percent of the city's audited nurseries were compliant with the NEMBA regulations, and that over fifty percent were stocking IAPs that have been regulated for at least thirteen years under a previous set of regulations (the Conservation of Agricultural Resources Act, CARA). This is despite high levels of awareness about the CARA regulations reported in the interviews, reported enthusiasm for compliance, apparent concern for the environment, evidence that managers understand the problems that IAPs cause, extensive reported support for the control of IAPs, and a reportedly strong sense of duty to protect the environment. The vast majority (73.5%) of IAP species found in nurseries were NEMBA category 1b invaders such as Nerium oleander, Lantana montevidensis and Canna indica. These are species that are widespread and well-established invaders that require control. This study suggests that a range of factors are likely to negatively influence compliance including a perceived lack of enforcement, weak communication from government, issues related to the clarity of the regulations, the lack of inclusion of the industry in the regulatory process, and a lack of awareness, with at least half of the managers reporting that they had not heard about the enactment of NEMBA. Any attempt to improve the impact of the new regulations will need to adequately address each of these factors. The results of the study suggest that enhancing the impact of NEMBA will require improving aspects of the legislation itself, and supplementing the current top-down approach to regulation with an inclusive partner-centred approach.